Management of Supply Chain Risk in Cattle Slice Fattening at PT. Catur Mitra Taruma - Aulia Rizky Elvandra; Mohamad Syamsul Maarif; Sukardi Sukardi (Indonesian Journal of Business and Entrepreneurship (IJBE), 2018)
PT Catur Mitra Taruma is one of the cattle fattening companies having a role as a source of beef cattle inventory for the beef processing industry. However, this company has the potential to experience a variety of supply chain risks that can hamper the company's business processes in carrying out its operational activities. The purpose of this study is to identify and analyze the risks that potentially appear in the process of supply chain beef cattle at PT. Catur Mitra Taruma, asses and evaluate identified risks, and formulate priority risk of mitigation and risk of chain action. The identification of supply chain risk was done using the dimensions of Supply Chain Operation Reference (SCOR). The method used in this study was the House of Risk method, an analysis that aims to identify and prioritize the source of risk for effective mitigation measures to minimize the potential risk and the source of existing risks. The identification results showed that the source process had the greatest risk of a total of 29 identified risk events in the company. In addition, there were 13 priority risk sources based on the ranking order of the priority risk index (ARP), rating of the total of 45 identified risk sources in the company. From the results of risk management analysis, there are recommendations of 10 priority risk mitigation actions that can be applied in PT. Catur Mitra Taruma in a potential supply chain risk prevention action in the company.Keywords: supply chain, supply chain risk, risk management, House of Risk, cattle fattening business